Leveraging mixed-effects location scale models to assess the ERP mismatch negativity’s psychometric properties and trial-by-trial neural variability in toddler-mother dyads - Mon, Serena K.; Manning, Brittany L.; Wakschlag, Lauren S.; Norton, Elizabeth S. (Developmental cognitive neuroscience, 2024)
Trial-by-trial neural variability, a measure of neural response stability, has been examined in relation to behavioral indicators using summary measures, but these methods do not characterize meaningful processes underlying variability. Mixed-effects location scale models (MELSMs) overcome these limitations by accounting for predictors and covariates of variability but have been rarely used in developmental studies. Here, we applied MELSMs to the ERP auditory mismatch negativity (MMN), a neural measure often related to language and psychopathology. 84 toddlers and 76 mothers completed a speech-syllable MMN paradigm. We extracted early and late MMN mean amplitudes from trial-level waveforms. We first characterized our sample’s psychometric properties using MELSMs and found a wide range of subject-level internal consistency. Next, we examined the relation between toddler MMNs with theoretically relevant child behavioral and maternal variables. MELSMs offered better model fit than analyses that assumed constant variability. We found significant individual differences in trial-by-trial variability but no significant associations between toddler variability and their language, irritability, or mother variability indices. Overall, we illustrate how MELSMs can characterize psychometric properties and answer questions about individual differences in variability. We provide recommendations and resources as well as example code for analyzing trial-by-trial neural variability in future studies. •Neural response variability may provide insight into development processes/disorders.•Mixed-effects location scale models (MELSMs) can isolate meaningful neural variability.•MELSMs fit data better than models that assumed constant variability.•Toddlers and mothers significantly vary in trial-by-trial ERP MMN variability.•Recommendations & code for trial-by-trial neural variability analyses are provided.